Rancang Bangun Sistem Informasi Penjualan Produk Berbasis Web Menggunakan Metode Agile Pada Risti Promotion - Lisanti, Sekar Wulan Ayu; Diartono, Dwi Agus (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Risti Promotion is a business engaged in the production and sale of souvenirs and raw materials. Risti Promotion is located on Jl. Sawah Besar RTO6 RW 03, Kaligawe Village, Gayamsari District, Semarang City. This home production focuses on making and selling products in the form of bags, wallets, dysgribs, and raw materials in the form of cloth. The problem with Risti Promotion is that the sales system still uses a manual system in the form of selling from seller to seller and the sales system has not been computerized. The existence of these problems causes various obstacles, such as difficulty in managing sales data, limited access to information about products, service delays, limited range of sales. So it took a while, vulnerable to problems. From this problem, a web-based sales system will be built using the Agile method. The development of systems with this method is because Agile methods are dynamic, so they can develop rapidly. The goals and results of building the system are to make it easier for business owners in Risti Promotion to manage product sales data and orders made by buyers, to make it easier for buyers to search for related product information, to reduce errors that may occur in the process of reporting and extracting product sales data.